More than words: a study on the visibility of hand gestures in public spaces - Kamil Kopij; Kaja Głomb; Szymon Popławski (Virtual Archaeology Review)
Hand gestures play an important role in human communication. Although the study of their repertoires and roles for past communities is a popular field of research, there has been no attempt so far to study their visibility during public events. The aim of this study was to determine the maximum number of people who could see hand gestures well enough to understand their meaning. Using gestures taken from ancient Roman rhetorical treatises, which we divided into three classes related to the detail of the gestures (fingers, hand, arm, or arms), we conducted a series of experiments to determine the maximum distance from which each class of gestures could be seen. We used the results, including regression analysis, to conduct visibility analyses for two case studies: one on the rostra on the Late Republican Forum Romanum in Rome; and the other on Pyramid No 3 in the centre of Late-Classical Mayan Tikal. We used the calculation of the areas where gestures were visible to estimate crowd sizes by drawing on crowd behaviour observation during contemporary public gatherings. They show not only how many people could have potentially seen the gestures, but also what percentage of the theoretically available space could have been occupied by people who had the potential to see them. According to the findings, only a little under half (44.8%) of the maximum possible audience were able to detect all types of gestures (various levels of detail) at the LR Roman Forum, while at Pyramid No 3 in Tikal, just a mere 16.7% were able to do so. We believe that the results presented and the methodology used can be applied to analyse any public space, regardless of place and time, thus providing a valuable tool to comprehend past public assemblies.